2021
DOI: 10.1002/2050-7038.13246
|View full text |Cite
|
Sign up to set email alerts
|

Optimal reactive power dispatch and distributed generation placement based on a hybrid co‐evolution algorithm and bi‐level programming

Abstract: To improve the economy and stability of distribution networks with a high penetration of distributed generation (DG), active management strategies should be considered during the planning stages and operating stage. This article presents a bi-level model of DG placement and an optimal reactive power dispatch, where the total investment and operation cost are minimized through an optimal allocation of the DG at the upper planning level, and the active power loss and voltage deviation are optimized based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…In formula (8), y is used to describe the device state signal after denoising; i represents the number of basic mode components; i e is used to describe the basic mode components after threshold processing; n represents the length of the basic mode component. By combining signal reconstruction, a noise-free operating state signal of power equipment can be obtained [20][21]. On this basis, it adopts DT technology to map the collected state signals into virtual and real ones, thereby constructing a dual-star model for the operation status of power equipment.…”
Section: Pemfc Operation Smo In View Of Dt Modelmentioning
confidence: 99%
“…In formula (8), y is used to describe the device state signal after denoising; i represents the number of basic mode components; i e is used to describe the basic mode components after threshold processing; n represents the length of the basic mode component. By combining signal reconstruction, a noise-free operating state signal of power equipment can be obtained [20][21]. On this basis, it adopts DT technology to map the collected state signals into virtual and real ones, thereby constructing a dual-star model for the operation status of power equipment.…”
Section: Pemfc Operation Smo In View Of Dt Modelmentioning
confidence: 99%
“…Khan et al introduced a modified salp swarm technique to address the ORPD; the technique boosted population variety and broadened the search field to produce high computational accuracy [23]. Chen et al utilized a combination of the co-evolution approach and bi-level planning to resolve the ORPD; this technique exhibited adequate reliability to decrease the active power loss [24]. Hosseini-Hemati et al indicated a superior grey wolf optimization to resolve the ORPD; this technique conveyed excellent dependability to arrive at the finest global solution [25].…”
Section: Introductionmentioning
confidence: 99%